Implication of Admission Eosinophil Count and Prognosis of Coronavirus Disease 2019 (COVID‐19) in Elderly Patients With COPD: A Territory‐Wide Cohort Study - Wang Chun Kwok; Yat Fung Shea; James Chung Man Ho; David Chi Leung Lam; Terence Chi Chun Tam; Anthony Raymond Tam; Mary Sau Man Ip; Ivan Fan Ngai Hung (The Clinical Respiratory Journal)
ABSTRACT Objectives This study aims to investigate the association between elderly patients with COPD with different blood eosinophil on admission and those without COPD and the prognosis of COVID‐19. Method A territory‐wide retrospective study was conducted to investigate the association between elderly COPD patients with different blood eosinophil on admission and the prognosis of COVID‐19. Elderly patients admitted to public hospitals and community treatment facility in Hong Kong for COVID‐19 from January 23, 2020, to September 31, 2021, were included in the study. Severe diseases were defined as those who develop respiratory complications, systemic complications and death. Results Among the 1925 patients included, 133 had COPD. Forty had admission blood eosinophil count ≥ 150 cells/μL, and 93 had blood eosinophil count < 150 cells/μL. Patients with COPD and admission blood eosinophil count ≥ 150 cells/μL, but not those with admission blood eosinophil count < 150 cells/μL, had severe COVID‐19 with the development of respiratory and systemic complications. They were more likely to develop respiratory failure (OR = 5.235, 95% CI = 2.088–13.122, p < 0.001) and require invasive mechanical ventilation (OR = 2.433, 95% CI = 1.022–5.791, p = 0.045) and intensive care unit admission (OR = 2.214, 95% CI = 1.004–4.881, p = 0.049). Discussion Our study suggested that the blood eosinophil count on admission could have significant prognostic implications among elderly patients with COPD. Patients with COPD and admission blood eosinophil count ≥ 150 cells/μL, but not those with admission blood eosinophil count < 150 cells/μL, have significantly increased risks of developing respiratory and systemic complications from COVID‐19, when compared with non‐COPD patients.